Architectural patterns for health information systems: a systematic review - Casanova, Rene; Villa-Garzon, Fernan A.; Branch-Bedoya, John W. (Frontiers in Digital Health, 2025)
BackgroundHealth information systems (HIS) are critical for digital health transformation, yet fragmentation and poor interoperability adoption remains a major challenge.ObjectivesThis study systematically reviews architectural patterns used in HIS and evaluates their alignment with ecosystem-level requirements.MethodsFollowing PRISMA 2020 guidelines, a systematic literature review was conducted across Scopus, IEEE Xplore, PubMed, and Web of Science (2020–2025). Eligible studies described, evaluated, or proposed HIS solutions.ResultsFrom an initial set of 304 records, 89 met the inclusion criteria. Service-based and decentralized/distributed ledger architectures were predominant, with emerging models integrating edge computing and modular design. FHIR-based contracts are found as stabilizers of interfaces, enabling validation and reducing integration costs. However, gaps persist in cross-border care, sustainability, and artificial intelligence integration.ConclusionWhile microservices dominate current HIS architectures, achieving resilient, interoperable ecosystems requires greater architectural diversity and intersectoral collaboration.